Enzymatic Interesterification of Palm Olein with Stearic Acid by Using Immobilized Pseudomonas Lipase - Yassin, Atif Abd Elmoneim Ahmed (2001)
Interesterification of palm olein with stearic acid by immobilized Pseudomonas lipase in n-hexane was studied. The catalytic performance of the immobilized Pseudomonas was evaluated by determining the change in fatty acid composition and concentration using gas liquid chromatography (GLC), and the change in triglyceride composition and concentration using high performance liquid chromatography (HPLC). Interesterification resulted in the formation of trisaturated triglyceride tripalmitin (PPP) and 1,2-dipalmitoyl-stearoyl glycerol (PPS), both of which were absent in the original oil. It also resulted in a decrease in the concentrations of the four main triglycerides in palm olein namely I-palmitoyl-dioleoyl glycerol (POO), 1,3-dipalmitoyl-2-oleoyl glycerol (POP), 1-palmitoyl-2-oleoyl-linoleoyl glycerol (POL) and 1,3-dipalmitoyl-2-linoleoyl glycerol (PLP). On the other hand, interesterification increased the concentrations of 1-stearoyl-dioleoyl glycerol (SOO), 1-palmitoyl-2-oleoyl-stearoyl glycerol (POS) and 1,3-distearoyl-2-0Ieoyl glycerol (SOS). Overall, the combined concentration of polyunsaturates, triunsaturates, and diunsaturates decreased, while that of the full saturates and mono unsaturates increased, thus raising the slip melting point of the final product. Interesterification caused substantial incorporation of stearic acid into the palm olein, with concomitant decreases in the palmitic and oleic acid contents. Immobilizing the Pseudomonas lipase resulted in a fast reaction, with the steady state reached after about 6 hours. Adding water to the reaction mixture increased the lipase activity.